If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 8) = 3(2x + 14) Reorder the terms: 2(8 + 2x) = 3(2x + 14) (8 * 2 + 2x * 2) = 3(2x + 14) (16 + 4x) = 3(2x + 14) Reorder the terms: 16 + 4x = 3(14 + 2x) 16 + 4x = (14 * 3 + 2x * 3) 16 + 4x = (42 + 6x) Solving 16 + 4x = 42 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 4x + -6x = 42 + 6x + -6x Combine like terms: 4x + -6x = -2x 16 + -2x = 42 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + -2x = 42 + 0 16 + -2x = 42 Add '-16' to each side of the equation. 16 + -16 + -2x = 42 + -16 Combine like terms: 16 + -16 = 0 0 + -2x = 42 + -16 -2x = 42 + -16 Combine like terms: 42 + -16 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
| y+7*0=11 | | 8k-7k-16*3k=-21 | | 2x-8=8x+6 | | 4/10=x/12 | | 7x+3=3x+75 | | x^2-4y^2-16y-20=0 | | 0=(8sinx)/x | | 5y+5(2+3)=4y+1 | | 5x+10=4(x-2) | | t^2+6t-20=0 | | 3[4(4+1)]= | | -20-6r=-4(2r+3) | | t^2+6-20=0 | | 3[f(4)(4)+1]= | | -x-29=11+4x | | 3x=5(16) | | f(x)=0x^0 | | 3x*x=147 | | 14-2+11+3= | | 5x+15=8x+2 | | 2(d+3)=28 | | f(x)=2x^1+0x^0 | | 15+5z=-10 | | -24-4x=15-x | | 3(m+1)=13 | | f/x | | 2[x-3(0)]= | | 3(5x-2)=4(2x+6) | | 10(c+7)=90 | | -8y+9=13 | | -7(2f+8)=-126 | | f(x)=3x^2+2x^1+0x^0 |